DRAMATURGI SANTRIWATI DALAM MENYIKAPI ATURAN BERPAKAIAN DI PONDOK PESANTREN RIYADLATUL ULUM LAMPUNG TIMUR - Ririn Jamiah; Siroy Kurniawan; Eka Listiana (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2024)
This research was conducted to find out how dramaturgy was carried out by santri at the Riyadhlatul Ulum Islamic boarding school, Batanghari, East Lampung. Dramaturgy in this case is the social life of the santri as seen from the front stage and back stage of Erving Goffman's theory of dramaturgy. This research is a qualitative research. Data collection techniques in this study used observation, interviews and documentation techniques. This research shows that the front stage is that female santri comply with the rules of dress in the pesantren environment such as not wearing trousers, skirts made of jeans and syar'i headscarves. While the back stage is the santri wearing clothes according to their wishes and the style of dress they like. There is one factor that causes this, namely social factors. Social factors include the school environment or campus environment. Friends who come from different backgrounds trigger the desire of the students to appear more attractive according to the style they want.